Methane and carbon dioxide seasonal cycles at urban Brazilian inland sites - Sikar, E.; La Scala, N. (Kluwer Academic Publ, 2004)
Methane and carbon dioxide seasonal cycles during years 1998 and 1999 at two Brazilian urban and inland sites are presented. The mixing ratio averages over the studied period of time were 1.80 ppm CH4 and 384.7 ppm CO2. A comparison is made between continental averages and the averages of the three nearest global network background sites of NOAA-CMDL comprising Ascension Island, Namibia and Easter Island. Inland sites had 0.08 ppm or 4.9% more CH4 and 19.0 ppm or 4.9% more CO2 than background over the same time span. The CH4 summer minimum observed in remote sites was also detected inland. During the month of October 98 and 99 inland mixing ratios were frequently similar to background.
Keywords: carbon dioxide; Methane; urban seasonal cycle